1982
DOI: 10.1111/j.1745-4514.1982.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting of Potatoes: Compositional Changes in Light and Dark

Abstract: The effect of sprouting in the light and dark on the contents of total nitrogen, nonprotein nitrogen, protein, total amino acids and minerals was assessed. Two varieties, Katahdin and Kennebec, and a clone, NY 61, were studied. I n all varieties, the sprouts were significantly (p < 0.01) higher than either cortex or pith tissues in total and nonprotein nitrogen. Protein and total amino acid content was highest in sprout tissue. Sprout tissue was also significantly (p < 0.01) higher in copper, zinc, magnesium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Tubers from plots receiving 40 lb/acre MgS04 discolored less and were lower in phenolic content and higher in crude lipid and phospholipid content than the controls. All levels of magnesium application (20, 40, and 100 lb/acre) resulted in firmer tubers containing more protein than controls (Klein et al, 1981(Klein et al, , 1982.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Tubers from plots receiving 40 lb/acre MgS04 discolored less and were lower in phenolic content and higher in crude lipid and phospholipid content than the controls. All levels of magnesium application (20, 40, and 100 lb/acre) resulted in firmer tubers containing more protein than controls (Klein et al, 1981(Klein et al, , 1982.…”
Section: Resultsmentioning
confidence: 89%
“…The amino acids alanine, leucine (Jadhav et al, 1973), glycine, serine (Nair et al, 1981), and arginine (Kaneko et al, 1976) have been reported to be incorporated into solanidine. Klein et al (1982) reported that magnesium fertilization increased levels of free amino acids and total amino acids. Alanine, arginine, glycine, leucine, and serine increased in the acid-hydrolyzable fraction with magnesium fertilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation